2016
DOI: 10.1016/j.neubiorev.2016.07.034
|View full text |Cite
|
Sign up to set email alerts
|

The role of experience in adolescent cognitive development: Integration of executive, memory, and mesolimbic systems

Abstract: Adolescence marks a time of unique neurocognitive development, in which executive functions reach adult levels of maturation. While many core facets of executive function may reach maturation in childhood, these processes continue to be refined and stabilized during adolescence. We propose that this is mediated, in part, by interactions between the hippocampus and pre-frontal cortex. Specifically, we propose that development of this circuit refines adolescents’ ability to extract relevant information from prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
86
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 145 publications
5
86
0
2
Order By: Relevance
“…It remains to be tested whether these circuits play functionally different roles in memory, with fine-scaled representation supporting decisions about relationships among detailed event elements and integration at broader scales supporting more abstract knowledge about the conceptual relationships among events. The fact that hippocampus and mPFC continue to mature through the third decade of life [85, 86] further suggests that memory integration may have a prolonged developmental timecourse that extends through adolescence, with corresponding impacts on spatial, temporal, and conceptual learning abilities. In reviewing the current state of knowledge on memory integration, we hope to inspire future work on the rich set of questions that remain.…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be tested whether these circuits play functionally different roles in memory, with fine-scaled representation supporting decisions about relationships among detailed event elements and integration at broader scales supporting more abstract knowledge about the conceptual relationships among events. The fact that hippocampus and mPFC continue to mature through the third decade of life [85, 86] further suggests that memory integration may have a prolonged developmental timecourse that extends through adolescence, with corresponding impacts on spatial, temporal, and conceptual learning abilities. In reviewing the current state of knowledge on memory integration, we hope to inspire future work on the rich set of questions that remain.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescent maturation is a useful framework to better understand if gyrification causally contributes to cognitive function because both brain structure and cognitive abilities change in characteristic developmental trajectories. Although executive and attention abilities are at near-adult levels by puberty, numerous studies describe they continue to be refined (Nguyen et al, 2016) and improve in various ways until about ages 15 to 17 (Best, 2010; Murty et al, 2016). These developmental trajectories offer a quasi-experimental context wherein one can determine if gyrification-cognition relationships differ across stages of adolescent cognitive development to see if decreasing regional gyrification has a functional impact on cognitive ability.…”
Section: Introductionmentioning
confidence: 99%
“…The limited work examining functional brain interactions is a major limitation, as complex behavioral processes likely arise through multiple brain regions interacting and sharing information with each other (van den Heuvel & Pol, 2010). With the hippocampus and vmPFC, functional interactions between these regions may be important for using previously acquired information in goal-directed behavior (Murty, Calabro, & Luna, 2016). For example, Gluth, Sommer, Rieskamp, and B€ uchel (2015) showed that decision making is limited by memory constraints, and this is associated with functional connectivity between the hippocampus and vmPFC.…”
mentioning
confidence: 99%